Insights two main products from the goat wine culture in the Brazilian Northeast (Research, Society and Development, 2022)
This review provides insights into the main products from goat and sheep farming, as well as their relevance to sociocultural development in Northeast Brazil. This study makes it possible to know the local production chain; it provides an understanding of how the types of management, culture, and level of technologies affect the final product, and how this directly affects the producer; and, therefore, makes it possible to identify useful strategies for improvements in the different production systems. The work was carried out from a descriptive approach and based on a literature review on the object of study, through the collection of electronic data (books and scientific publications). In conclusion, it is observed that there is a promising market at the national and international level that still needs to be explored and adequate, thus ensuring the expansion of products (meat and dairy) and by-products (skin, manure, and viscera) of goats and sheep.